The Inhibition of Cathepsin G on Endometrial Explants With Endometrosis in the Mare - Amaral, Ana; Fernandes, Carina; Morazzo, Sofia; Rebordão, Maria Rosa; Szóstek-Mioduchowska, Anna; Lukasik, Karolina; Gawronska-Kozak, Barbara; Telo da Gama, Luís; Skarzynski, Dariusz Jan; Ferreira-Dias, Graça (Frontiers in Veterinary Science, 2020)
Although proteases found in neutrophil extracellular traps (NETs) have antimicrobial properties, they also stimulate collagen type 1 (COL1) production by the mare endometrium, contributing for the development of endometrosis. Cathepsin G (CAT), a protease present in NETs, is inhibited by specific inhibitors, such as Cathepsin G Inhibitor I (INH; β-keto-phosphonic acid). Metallopeptidases (MMPs) are proteases involved in the equilibrium of the extracellular matrix. The objective of this study was to investigate the effect of CAT and INH (a selective CAT inhibitor) on the expression of MMP-2 and MMP-9 and on gelatinolytic activity. In addition, the putative inhibitory effect of INH on CAT-induced COL1 production in mare endometrium was assessed. Endometrial explants retrieved from mares in follicular phase or mid-luteal phase were treated for 24 or 48h with CAT, inhibitor alone, or both treatments. In explants, transcripts (qPCR) of COL1A2, MMP2 and MMP9, as well as the relative abundance of COL1 protein (western blot), and activity of MMP-2 and MMP-9 (zymography) were evaluated. The protease CAT induced COL1 expression in explants, at both estrous cycle phases and treatment times. The inhibitory effect of INH was observed on COL1A2 transcripts in follicular phase at 24h treatment, and in mid-luteal phase at 48h (P < 0.05), and on the relative abundance of COL protein in follicular phase and mid-luteal phase explants, at 48h (P < 0.001). Our study suggests that MMP-2 might also be involved in an earlier response to CAT, and MMP-9 in a later response, mainly in the follicular phase. While the use of INH reduced CAT-induced COL1 endometrial expression, MMPs might be involved in the fibrogenic response to CAT. Therefore, in mare endometrium, the use of INH may be a future potential therapeutic means to reduce CAT induced COL1 formation, and to hamper endometrosis establishment.